KEPATUHAN PAJAK DAN REPUTASI PERUSAHAAN - A. Ragil Kuncoro (JURNAL PAJAK INDONESIA, 2021)
Reputation risk is at the top of the list of risks faced by companies (Ernst & Young, 2014). Reputation is the net result of various stakeholders' perceptions of how they meet their expectations (Fombrun, 2000). Six factors determine a company's reputation, namely compliance with government regulations; company code of ethics; management's treatment of people within the company; company operations, and the company's response to environmental issues (Honey, 2009). However, there are not many papers that discuss the effect of tax compliance on a company's reputation. Using panel data regression of publicly listed companies in Indonesia in 2016-2019, this study examines the hypothesis of tax compliance on the reputation of companies. The results showed that tax compliance positively affects the company's reputation.